Description and evaluation of the rehabilitation programme for persons with lower limb amputations at Elangeni, Paarl, South Africa - Fredericks, Jerome P. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.